Progressive Collapse of RC Frame Under Different Levels of Damage Scenarios - Ilyas, U.; Farooq, S. H.; Qazi, A. U.; Ilyas, M. (The Nucleus, 2018)
<span style="font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Progressive Collapse analysis of Reinforced Concrete (RC) frame was carried out using commercial software i.e. SAP2000. The RC frame consisting of nine stories was selected and designed as per Pakistan Building Code. Two damage patterns were considered for the progressive collapse analysis; damage at corner column and damage at edge column. The General Services Administration loading criterion is followed to carry out Linear Static Analysis with 40%, 80% and fully damaged scenarios. In addition to Linear Static Analysis, Nonlinear Linear Static Analysis and Nonlinear dynamic Analysis was also carried out to assess the vulnerability of the structure exposed to progressive collapse. After that results were analyzed to determine the nature and intensity of structural damage due to column failure. It was found that edge column with longer spans has more damage potential as compared with smaller spans in Linear Static Analysis. However, in Non Linear Static Analysis and Non Linear Dynamic Analysis, the hinges are at their initial stages in all cases and progressive collapse is less critical. Therefore, Linear Static Analysis based on General Services Administration guidelines is more conservative than Nonlinear Linear Static Analysis and Non Linear Dynamic Analysis.